2016
DOI: 10.1007/s00128-016-1761-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Eco-Risk Assessment of Heavy Metals in the Surface Soils of Industrial City of Aran-o-Bidgol, Iran

Abstract: Heavy metals usually accumulate and migrate in soil environment due to human activities and this in return poses potential ecological and health risks. A total of 135 surface soil samples were collected from Aran-o-Bidgol City, Iran and were analyzed for their Cd, Pb, Ni and Cu concentrations to determine these elements' spatial distribution and potential ecological risks. To this end, interpolation mapping was conducted using Ordinary Kriging. The mean concentrations of Cd, Pb, Ni and Cu in the samples were 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 35 publications
(44 reference statements)
0
7
1
Order By: Relevance
“…From this point of view, they seemed to exert more indirect influences. Cu, Pb, and Zn have often been traffic-related in urban environments in previous studies [51][52][53]. However, with a slight difference, we found that industrial emissions determined the soil pollution with Cu while it was the soil properties for Pb.…”
Section: Scale-dependent Drivers Of Spatial Variations In Soil Pollutioncontrasting
confidence: 55%
“…From this point of view, they seemed to exert more indirect influences. Cu, Pb, and Zn have often been traffic-related in urban environments in previous studies [51][52][53]. However, with a slight difference, we found that industrial emissions determined the soil pollution with Cu while it was the soil properties for Pb.…”
Section: Scale-dependent Drivers Of Spatial Variations In Soil Pollutioncontrasting
confidence: 55%
“…The potential ecological risk index (RI) was used to evaluate the risk of heavy metals in soil and sediment near the tailings pond. The potential ecological risk index considers not only the content of heavy metals, but also the ecological effect, environmental effect, and toxicological effect of heavy metals [ 28 , 29 ]. The potential ecological risk index RI was calculated using the following equation [ 30 ]: where RI is the potential ecological index for the sampling point; is the potential ecological risk index of a particular heavy metal I ; is the toxic-response factor for the given heavy metal I ; is the concentration of heavy metal i in soil or sediment; is the background value of the heavy metal i in soil or sediment ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The potential ecological risk index (RI) was used to evaluate the risk of heavy metals in soil and sediment near the tailings pond. The potential ecological risk index considers not only the content of heavy metals, but also the ecological effect, environmental effect, and toxicological effect of heavy metals [28,29]. The potential ecological risk index RI was calculated using the following equation [30]:…”
Section: Potential Ecological Risk Indexmentioning
confidence: 99%
“…Calculations of the various factors of ecological pollution demonstrated that Cd was the main contributor to enhanced RI. Ravankhah et al [27] found the average pollution of Pb, Cu, and Cd in the soil of Arano-Bidgol to be 11.41, 14.82, and 0.72 mg kg −1 , respectively, all of which were greater than their reference quantities. Considering the RI values and reference quantities, this area showed a comparably great level of pollution.…”
Section: Introductionmentioning
confidence: 94%
“…The means of the RI for the agricultural land, rangeland, and urban land uses were 114.09, 122.08, and 339.62, respectively. Among all, the urban land use showed the highest RI for its inhabitants [1,27].…”
Section: Cf Er and Ri Assessments In The Urban Field Soilsmentioning
confidence: 99%